2023
DOI: 10.1038/s41594-023-01011-w
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of GABA transporter 1 reveals substrate recognition and transport mechanism

Abstract: The inhibitory neurotransmitter γ-aminobutyric acid (GABA) is cleared from the synaptic cleft by the sodium- and chloride-coupled GABA transporter GAT1. Inhibition of GAT1 prolongs the GABAergic signaling at the synapse and is a strategy to treat certain forms of epilepsy. In this study, we present the cryo-electron microscopy structure of Rattus norvegicus GABA transporter 1 (rGAT1) at a resolution of 3.1 Å. The structure elucidation was facilitated by epitope transfer of a fragment-antigen binding (Fab) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The importance of sodium for substrate transport has been characterised at the macroscopic and the kinetic level (Hilgemann and Lu, 1999;Iversen and Snyder, 1968;Mager et al, 1993) and showed that GABA uptake is energised by the downhill concentration gradient of the co-transported sodium (Kanner, 1978). Structural data of transporters from the SLC6 family have revealed the binding sites of substrate and co-transport ions and the main conformations of the transport cycle of GAT1 (Nayak et al, 2023;Zhu et al, 2023). We confirmed through direct observations that NA2 functions to stabilise GAT1 in the outward-open conformation and showed that Na2 achieves this by immobilising the scaffold and bundle domains in relation to each other.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The importance of sodium for substrate transport has been characterised at the macroscopic and the kinetic level (Hilgemann and Lu, 1999;Iversen and Snyder, 1968;Mager et al, 1993) and showed that GABA uptake is energised by the downhill concentration gradient of the co-transported sodium (Kanner, 1978). Structural data of transporters from the SLC6 family have revealed the binding sites of substrate and co-transport ions and the main conformations of the transport cycle of GAT1 (Nayak et al, 2023;Zhu et al, 2023). We confirmed through direct observations that NA2 functions to stabilise GAT1 in the outward-open conformation and showed that Na2 achieves this by immobilising the scaffold and bundle domains in relation to each other.…”
Section: Discussionmentioning
confidence: 99%
“…The motion of the bundle domain relative to the scaffold domain allows for alternating access to the central substrate binding site S1 (Forrest et al, 2008). Very recently, several inward-facing GAT1 structures and a substrate, sodium and chloridebound inward-occluded structure were published (Motiwala et al, 2022;Nayak et al, 2023). These conformations together with an AlphaFold2 model of the outward-facing state have allowed to formulate the translocation cycle for GAT1 (Nayak et al, 2023;Zhu et al, 2023) which consists of outward-open, occluded and inward-open states.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations